Analysis of organic components in resin‐modified pulp capping materials: critical considerations. (26th April 2017) - Nilsen, Bo W.; Jensen, Einar; Örtengren, Ulf; Michelsen, Vibeke B.
Abstract : The purpose of this study was to elucidate the organic composition and eluates of three resin‐based pulp‐capping materials in relation to their indications and safety data sheets. Uncured samples of Theracal LC, Ultra‐Blend Plus, and Calcimol LC were investigated using gas chromatography–mass spectrometry (GC‐MS) and ultra‐performance liquid chromatography–mass spectrometry (UPLC‐MS). Identification/quantification of 7‐d leachables of cured samples was performed using GC‐MS for 2‐hydroxyethyl methacrylate (HEMA), 2‐(dimethylamino)ethyl methacrylate (DMAEMA), camphorquinone (CQ), ethylene glycol dimethacrylate (EGDMA), ethyl‐4‐(dimethylamino)benzoate (DMABEE), and triethylene glycol dimethacrylate (TEGDMA). A similar organic composition was found for Ultra‐Blend and Calcimol; however, only Ultra‐Blend is indicated for direct pulp‐capping. In contrast to the other materials analysed, Theracal contained substances of high molecular weight. The safety data sheets of all materials were incomplete. We detected HEMA, CQ, and TEGDMA in eluates from Ultra‐Blend and Calcimol, and it was considered that HEMA might have originated from decomposition of diurethane dimethacrylate (UDMA) in the GC‐injector. For Theracal, additives associated with light curing (DMABEE and CQ) were detected in higher amounts (4.11 and 19.95 μ g mm −2 ) than in the other materials. Pores were quantified in all samples by micro‐computed tomography (micro‐CT) analysis, which could influence leaching. The organic substances in the investigated materials might affect their clinical suitability as capping agents, especially for direct capping procedures.